Is It Essential for Occupational Health and Safety Experts to Know the English Language? Results From Several Studies in Latvia - Matisāne, Linda; Paegle, Linda; Akūlova, Lāsma; Eglı̄te, Maija; Vanadziṇš, Ivars (Frontiers in Public Health, 2022)
Background Poor knowledge of the language has been identified as a barrier to up-to-date occupational safety and health information, however, this question has not been addressed in the context of occupational safety and health expert competence in providing advice for employers in a small, non-English speaking country. Objectives To analyze the available data on the use of languages for searching professional information by occupational safety and health (OSH) experts, and the sources of information on COVID-19 during the first wave of the pandemic in Latvia, and to assess if the knowledge of the English language among these experts is sufficient to react rapidly and effectively in case of emergency. Methods Data were compiled from several different sources: three web-based surveys of occupational safety and health experts (data from 2006, 2010, and 2018) and ten focus group discussions with employers and occupational safety and health experts (data from 2020). Results The results of the surveys show that between 2006 and 2018, the percentage of respondents using only one language (Latvian) for searching professional information in occupational safety and health has increased from 25 to 35.3%. In 2018, the English language was mentioned by only 42.8% of respondents and Russian by 46.8%. During the focus group discussions, the use of English was mentioned for obtaining trustful information from international organizations, for analysis of information received within international companies, for searching international experience, and for finding county-specific information. Discussion Our study shows that knowledge of the English language for occupational safety and health experts working in Latvia is not sufficient. The companies providing external occupational safety and health services should establish a well-functioning internal training system to provide their non-English speaking experts with up-to-date information. Occupational safety and health-related non-governmental institutions should strengthen their capacity in sharing information related to different occupational safety and health aspects into the national language (Latvian in this particular case).